Six Lies (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
Composed in a fiction writing workshop, Six Lies is a story that seeks to address themes of family, trauma, and cats.For additional context, listen to the author's reflection on the piece below.